The Influence of Candidate Figures and Perception of Leadership Quality on Electa-bility in The Regional Head Election of DKI Jakarta - Syony Tjahjadi (Eduvest - Journal of Universal Studies, 2024)
The election of regional leaders is an important agenda in the democratic system in Indonesia, which has significant implications for the direction of policies and development in a region. This research examines the influence of candidate figures and perceptions of leadership quality on electability in the Jakarta Regional Head Election, considering the complexity of issues and high development challenges in the area. This study uses a quantitative approach by distributing questionnaires to 85 respondents who are samples of the Jakarta community eligible to vote. The measured variables include candidate figures, perceptions of leadership quality, and electability. Data analysis is conducted using Partial Least Squares - Structural Equation Modeling (PLS-SEM) through the Smart PLS software. The research findings indicate that credibility does not have a significant influence on the electability of leaders, while capability and perceptions of leadership have a positive and significant influence. Perceptions of leadership have the greatest influence on the electability of leaders compared to other factors. These findings indicate that the people of Jakarta prioritize the capabilities of potential leaders, which include educational background, professional experience, and organizational involvement. However, the most influential factor is a positive perception of leadership, including the vision, mission, competence, and integrity of potential leaders.